1995
DOI: 10.1136/jech.49.4.431
|View full text |Cite
|
Sign up to set email alerts
|

The ten questions screen for childhood disabilities: its uses and limitations in Pakistan.

Abstract: Objective -To assess the accuracy of the ten questions screen as a measure ofchildhood disability for epidemiologic studies in populations lacking resources for professional assessment of children's development and functioning. Design -Household survey and screening of children in phase one followed by clinical assessments in phase two. Setting -Karachi, Pakistan. Participants -A cluster sample of 6365 children, aged 2 to 9 years, screened using the ten questions and a subsample referred for clinical assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 15 publications
0
64
3
Order By: Relevance
“…When dialed, the IVR application provided prerecorded voice-responses to the Ten Questions Screen for disability. 14 After each prerecorded question had been read out, the caller was given the choice to select options by pressing a digit. When all 10 questions had been answered, the application used an algorithm to determine the results of the screening and fed it back to the caller.…”
Section: Figurementioning
confidence: 99%
“…When dialed, the IVR application provided prerecorded voice-responses to the Ten Questions Screen for disability. 14 After each prerecorded question had been read out, the caller was given the choice to select options by pressing a digit. When all 10 questions had been answered, the application used an algorithm to determine the results of the screening and fed it back to the caller.…”
Section: Figurementioning
confidence: 99%
“…This questionnaire screens for the presence of neurodevelopmental disabilities. 6 It has been validated in similar geographic and economic contexts for children as young as 2 years old, 7 and shows good (85%) sensitivity in the detection of moderate to severe disabilities in children older than 2 years. Children without developmental abnormalities may screen positive on the Ten Questions Screen due to a history of febrile seizure.…”
mentioning
confidence: 99%
“…Overall, 15.59% of children aged 2-9 years were estimated to have some impairment and 10.06% of children were estimated to have a disability, of which cognition was by far the most prevalent condition. The prevalence estimate for Cambodia, of 3.22% for children aged 2-9 years with moderate/severe/ profound disabilities, was similar to figures for Jamaica at 2.5% (Thorburn et al, 1992) and Pakistan at 4.4% (Durkin et al, 1995) but lower than that found in Kenya at 6.1% (Mung'ala-Odera et al, 2006).…”
Section: Discussionmentioning
confidence: 55%
“…The Organisation for Economic Cooperation and Development (OECD, 2007) gives a median percentage for 15 developed countries of 2.63% for children with organic disabilities of compulsory school age, and data from developing countries, e.g. Jamaica at 2.5% (Thorburn et al, 1992) and Pakistan at 4.4% (Durkin et al, 1995) and Kenya at 6.1% (Mung'alaOdera et al, 2006), all show estimates substantially higher than 1%.…”
Section: Introductionmentioning
confidence: 99%